Toll-Like Receptor Evolution: Does Temperature Matter? - Sousa, Cármen; Fernandes, Stefan A.; Cardoso, João C. R.; Wang, Ying; Zhai, Wanying; Guerreiro, Pedro M.; Chen, Liangbiao; Canário, Adelino V. M.; Power, Deborah M. (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) recognize conserved pathogen associated molecular patterns (PAMPs) and are an ancient and well conserved group of pattern recognition receptors (PRRs). The isolation of the Antarctic continent and its unique teleost fish and microbiota prompted the present investigation into Tlr evolution. Gene homologues of tlr members in teleosts from temperate regions were present in the genome of Antarctic Nototheniidae and the non-Antarctic sister lineage Bovichtidae. Overall, in Nototheniidae apart from D. mawsoni no major tlr gene family expansion or contraction occurred. Instead, lineage and species-specific changes in the ectodomain and LRR of Tlrs occurred, particularly in the Tlr11 superfamily that is well represented in fish. Positive selective pressure and associated sequence modifications in the TLR ectodomain and within the leucine-rich repeats (LRR), important for pathogen recognition, occurred in Tlr5, Tlr8, Tlr13, Tlr21, Tlr22 and Tlr23 presumably associated with the unique Antarctic microbiota. Exposure to lipopolysaccharide (Escherichia coli O111:B4) from bacteria did not modify tlr gene expression in N. rossii head-kidney or anterior intestine, although increased water temperature (+2ºC) had a significant effect.